Use of Modern Technologies which are Significant in Teaching the Subject "Chemistry of Biogenic Elements" (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
It is shown what modern pedagogical technologies should be used to explain the topic "Chemistry of biogenic elements".